Rugby skills, tactics, and rules - Williams, Tony, 1960- (Firefly Books, 2008)
A comprehensive guide to rugby, packed with action photos of great players. The authors, experts with international experience as players and coaches, describe the many tactical and skill aspects of the game. Fully updated.